KARAKTERISTIK DAN PERJALANAN DERMATITIS ATOPIK DENGAN RIWAYAT ASMA BRONKIAL - Abelia, Anisa Dwi (Surabaya Biomedical Journal, 2023)
Atopic dermatitis is a chronic inflammatory skin disease that begins primarily in childhood with a mixed natural history. atopic dermatitis has increased over the past 30 years. It is currently estimated that 10-20% of children and 1-3% of adults in developed countries are affected by atopic dermatitis. Knowing the characteristics and course of atopic dermatitis with a history of bronchial asthma based on: Gender, age, history of atopy, signs and symptoms, location of lesions and disease course and development including disease onset. This research method uses literature study. Where this research contains explanations, elaboration of theories, findings, and search results regarding topics written from books, journals, articles and research reports. Researcher questions and topics are matched with specific keywords for research. These keywords are then used to search for articles on Google Scholar, PubMed, and Science Direct. These articles are then sorted and categorized into PRISMA diagrams. Then proceed with filtering and indexing articles on Scimago or SINTA. It was found that 15 of these indexing results were found in Scimago or SINTA. Characteristics of atopic dermatitis with a history of bronchial asthma found the majority to occur in women. The onset begins in childhood, gets better in adolescence and then gets worse in adulthood. The characteristic lesions of atopic dermatitis, in which one reported dry and itchy skin to erythema, skin peeling, skin thickening, secretions, hyperpigmentation, and lichenification. There is an increase in IgE and pro-Th2 cytokine levels, based on the therapy the majority indicate the use of corticosteroids. Keywords : atopic dermatitis, asthma bronchiale, allergy